Promises and Social Distance in Buyer-Determined Procurement Auctions - Timo Heinrich; Jeannette Brosig-Koch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study explores the effects of communication and its interaction with reputation information. Our focus is on buyer-determined procurement auctions with moral hazard in which buyers can select a bidder based on prices and all other information available. The results of our controlled laboratory experiment demonstrate that in contrast to reputation information communication only slightly increases market efficiency. If reputation information is available, communication has no additional efficiency effect. Buyers' choice of a bidder is influenced by both, reputation information and the content of communication. Specifically, buyers prefer bidders with a good reputation and bidders who promise them a specific profit. If this kind of promise is infeasible as it is often the case in real auctions, buyers prefer bidders whose argu-ments reduce social distance. Unspecific promises have no significant effect. Using a unique set of field data, we compare observed buyer choices with those in the field and find a choice pattern that is consistent with our lab data. High reputation bidders and bidders reducing social distance by initiating communication through additional channels are more likely to be selected as auction winners.
Keywords: C91; D83; D44; 330